Decoding Survival in Elderly Acute Myocardial Infarction: The Prognostic Interplay of B-Type Natriuretic Peptide, Ejection Fraction, and Renal Function – An Observational Study - Rajpal Prajapati; Abhishek Kapoor; Salini Mukhopadhyay; Arjun Tandon; Soumik Ghosh; Om Shankar (Journal of the Indian Academy of Geriatrics, 2025)
Background: B-type natriuretic peptide (BNP) is a well-established biomarker of myocardial stress and heart failure, yet its role in predicting short-term survival in elderly acute myocardial infarction (AMI) patients, particularly in relation to left ventricular ejection fraction (LVEF) and renal function, remains underexplored. This study evaluates the correlation between plasma BNP levels, LVEF, and estimated glomerular filtration rate (eGFR) and their prognostic significance in geriatric AMI patients managed conservatively. Materials and Methods: This prospective observational study was conducted at a tertiary care hospital in Northern India over 2 years (January 2022–December 2023). Patients aged ≥ 60 years with AMI were included in this study, while those with preexisting end-stage renal disease, significant valvular heart disease, or those undergoing percutaneous coronary intervention or coronary artery bypass grafting were excluded from the study. BNP levels were measured within 48 h of symptom onset. LVEF was assessed through echocardiography, and renal function was estimated using the modification of diet in renal disease formula. Statistical analysis included Pearson’s correlation, Student’s t-test, ANOVA, and multivariate logistic regression to evaluate associations between BNP, LVEF, eGFR, and mortality. Results: Among 369 patients (mean age: 69 ± 8.2 years; 61% male), non-ST elevation myocardial infarction was the predominant diagnosis (74%). The mean LVEF was 47.1%, mean eGFR was 65.2 mL/min/1.73 m2, and median BNP was 1021.6 pg/mL. Patients who succumbed to myocardial infarction (15% mortality rate) had significantly lower eGFR (47.07 vs. 64.06 mL/min/1.73 m2, P = 0.005) and LVEF (41.31% vs. 47.36%, P = 0.01), while BNP levels were markedly higher in nonsurvivors (1766.8 vs. 1002.7 pg/mL, P = 0.001). BNP demonstrated a moderate inverse correlation with both eGFR (r = −0.68, P < 0.001) and LVEF (r = −0.56, P = 0.005). Multivariate logistic regression confirmed BNP, eGFR, and LVEF as independent predictors of in-hospital mortality (P < 0.05). Conclusion: Elevated BNP, reduced LVEF, and impaired renal function are independent predictors of mortality in geriatric AMI patients. BNP levels strongly correlate with both cardiac and renal dysfunction, underscoring its role as a key biomarker in risk stratification. These findings emphasize the need for BNP evaluation in clinical decision-making for elderly AMI patients, particularly in resource-limited settings where immediate intervention may not always be feasible. Further large-scale, multi-center studies are warranted to refine risk assessment models and optimize management strategies in this high-risk population.